Studi Perspektif Pemuda tentang Regenerasi Sektor Pertanian: Studi Kasus di Kabupaten Karanganyar - Ali Zainal Abidin; Muhammad Randhy Kurniawan; Kenny Pradipta Montoya Putra Pratama; Handy Nugraha (Jurnal Sosial Ekonomi Pertanian, 2026)
Abstract The agricultural sector plays a strategic role in supporting food security and sustainable economic development. However, this sector faces serious challenges in labor regeneration due to the low interest of younger generations in participating. The decline in youth involvement has the potential to threaten the sustainability of food production as well as the economic stability of rural areas. Although the issue of farmer regeneration has been widely discussed, in-depth studies examining youth perceptions of the agricultural sector at the local level remain relatively limited. This study aims to analyze youth perceptions of the agricultural sector in Karanganyar Regency and to examine the role of stakeholders in supporting the regeneration of the agricultural workforce. The research employs a qualitative approach with a case study method, using in-depth interviews with ten young people from both farming and non-farming families. Data were analyzed using content analysis techniques with source triangulation. The findings indicate that negative perceptions—such as the view that agriculture is synonymous with physically demanding work, high risk, and limited economic prospects—are the main factors contributing to low youth interest. However, the adoption of modern agricultural technologies, agribusiness-based education, and policy support have been shown to increase the attractiveness of the sector to younger generations. These findings highlight the importance of policies oriented toward agricultural modernization, the strengthening of technology-based education, and the renewal of the agricultural sector’s image to accelerate the regeneration of young farmers. Keywords: Farmer Regeneration; Youth Perceptions; Agricultural Technology; Agricultural Policy; Food Security